Characterization of quince (Cydonia oblonga Mill.) cultivars using SSR markers developed for apple - Halász, J.; Hoffman, V.; Szabó, Z.; Nyéki, J.; Szabó, T.; Hegedűs, A. (International Journal of Horticultural Science, 2009)
Quince (Cydonia oblongaMill.) is a minor fruit crop, which is primarily used for marmalade, jam and sauce.Very few quince cultivars are known all over the world and in many cases similar names are used for presumably different cultivars. The aim of the present study was to evaluate and characterize the genetic diversity of 36 quince cultivars and selections with SSR markers. Seven out of 8 SSR markers designed from apple sequences could successfully yield amplification also in quince cultivars. Number of alleles per locus ranged from 2 to 3 alleles. These allele numbers are quite low when compared to apple. It is supposed to be the consequence of a genetic bottleneck. In spite of the low allele number per locus, the 36 quince cultivars formed 30 different genotypes. The ratio of homozygosity was low, which might be coupled with the self-(in)compatibility phenotype of quinces. SSR markers proved unable to differentiate putatively closely related cultivars (e.g. ‘Bereczki’ and ‘Bereczki bôtermő’). In general, the level of polymorphism among the tested quince genotypes was much restricted due to the low allele number detected. However, it must be considered that the number of analysed SSR loci is not enough high to estimate the overall heterozygosity of the quince genome. Further experiments are needed and the SSR markers proved to be a reliable and useful tool for such analyses.